Osteonecrosis of the jaw associated with receiving sunitinib monotherapy: A rare case. Issue 1 (January 2021) - Takahara, Toshikazu; Shimada, Ken; Ishida, Sho; Ishida, Nao; Yoshimura, Shusaku; Takeuchi, Shin; Saito, Tomoaki; Miyamoto, Isao; Baba, Takako; Saito, Kengo; Minakawa, Yasuyuki; Nakatsuru, Makoto
Abstract: Sunitinib is an antiangiogenic drug for the treatment of metastatic renal cell carcinoma (mRCC) and imatinib-resistant gastrointestinal stromal tumor (GIST). Toxicities derived from sunitinib, such as altered taste, dry mouth, mucosal sensitivity, oral pain, gingival bleeding, and oral mucositis/stomatitis (OM/S) are widely reported. Additionally, in recent years, osteonecrosis of the jaw (ONJ) is reported to be related with sunitinib. We present here a rare case of ONJ involving mRCC receiving sunitinib monotherapy. A-76-year-old man, treated with sunitinib only, complained about oral pain in April 2019. In the lower mandibular, bone exposure and stomatitis were observed. The patient did not receive bisphosphonates or denosumab. Furthermore, he has not undergone tooth extraction or worn a denture in the left mandibular region. Panoramic radiograph and computed tomography (CT) did not show any obvious radiological changes or bone pathology. During the follow up, healing and bone exposure were repeated with sunitinib dosing and withdrawal. Finally, 3 months later (July 2019), a diameter of 3 × 3 mm necrotic bone was exposed and separated from the left lower mandible. Finally, sunitinib-related jaw osteonecrosis diagnosis was made.